Central banking financial vs piramides (2009)
But why should the pyramid schemes fail? Why can not continue forever, riding on the back of new money and keeping every happy, new and old investor? Is it stable? Is it liquid? Is the asset portfolio diversified enough? Nobody knows. The fog even those who created it in the first place. No appropriate financial control and possible intervention under such circumstances. The pyramids are among the dishonest schemes for common oldest consumer. The pyramids are illegal and fail. People will lose their money. This paper has been prepared to help you understand the differences between legal and fraudulent business not to seek to solve the problem, we see the pyramids have had more impact on the course of history, the Colombian case and regulations governing entities obtain resources from the public and reach resover this concern is there any real standard for legal authorities shut down a pyramid scheme? Participants may be fined or arrested.? The pyramids are misleading? Participants in a pyramid, like it or are not deceiving the people you recruit? Few people would be fooled if they fully explain the risks? Reach your own conclusion?